Prescriptions for home hemodialysis. (April 2015) - Lockridge, Robert; Cornelis, Tom; Van Eps, Carolyn
Abstract: Prescribing a regimen that provides "optimal dialysis" to patients who wish to dialyze at home is of major importance, yet there is substantial variation in how home hemodialysis (HD) is prescribed. Geographic location, patient health status and clinical goals, and patient lifestyle and preferences all influence the selection of a prescription for a particular patient—there is no single prescription that provides optimal therapy for all patients, and careful weighing of potential benefit and burden is required for long‐term success. This article describes how home HD prescribing patterns have changed over time and provides examples of commonly used home HD prescriptions. In addition, associated clinical outcomes and adequacy parameters as well as criteria for identifying which patients may benefit most from these diverse prescriptions are also presented.